2018
DOI: 10.3892/ol.2018.8457
|View full text |Cite
|
Sign up to set email alerts
|

Exosome‑encapsulated microRNA‑223‑3p as a minimally invasive biomarker for the early detection of invasive breast cancer

Abstract: Patients diagnosed preoperatively with ductal carcinoma (DCIS) breast cancer have the potential to develop invasive ductal carcinoma (IDC). The present study investigated the usefulness of exosome-encapsulated microRNA-223-3p (miR-223-3p) as a biomarker for detecting IDC in patients initially diagnosed with DCIS by biopsy. The potential association between miR-223-3p and clinicopathological characteristics was examined in patients with breast cancer. Exosomes of 185 patients with breast cancer were separated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 26 publications
3
70
1
Order By: Relevance
“…Interestingly, miR‐192‐5p, miR‐19a‐3p, and miR‐19b‐3p were still upregulated in exosomes as in serum and tissues. Though exosome‐encapsulated miR‐223‐3p was once reported to be noninvasive biomarker for breast cancer, no significant statistical difference was observed for PC in this study . To date, there were still few reports being published on the exosomes miRNAs characteristics of PC patients.…”
Section: Discussioncontrasting
confidence: 59%
“…Interestingly, miR‐192‐5p, miR‐19a‐3p, and miR‐19b‐3p were still upregulated in exosomes as in serum and tissues. Though exosome‐encapsulated miR‐223‐3p was once reported to be noninvasive biomarker for breast cancer, no significant statistical difference was observed for PC in this study . To date, there were still few reports being published on the exosomes miRNAs characteristics of PC patients.…”
Section: Discussioncontrasting
confidence: 59%
“…Levels of serum exo-miR-1290 and exo-miR-375 are associated with castration resistance in prostate cancer (39). miR-223-3p encapsulated by exosomes has been identified as an important biomarker for the early detection of invasive breast cancer (40). Exo-miR-423-5p has been reported as a minimally invasive biomarker in the diagnosis of gastric cancer, and can promote tumor growth and metastasis by targeting SUFU negative regulator of hedgehog signaling (41).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of initial studies investigating circulating EV-miRNAs as biomarkers of breast cancer in recent years [5,[16][17][18][19][20][21]. Although limited by control sample size, one study reported elevation of miRNA-101 and miRNA-372 in serum-derived EVs of patients with breast cancer (n = 50) compared to healthy controls (n = 12) [5].…”
Section: Introductionmentioning
confidence: 99%